Aging and Visual Presentations in MRI Environments. Issue 1 (March 2023) - Walker, Jenny; Kumar, Rachit; Hoo, Marvin; Wheeler, Mark E.
As individuals age, their vision tends to decline. These changes are natural, but often neglected when designing tasks for both older and younger adults. For instance, many MRI machine set-ups include in-bore displays. Ongoing work in our lab suggests that some older adults have issues seeing stimuli on these displays if there is a visual noise component. This is a problem that did not occur with younger adult samples. Therefore, this work provides an example of how this concern was addressed using a psychophysical thresholding technique. We hope that our experience will inform others who are facing similar issues and/or seeking suggestions for improving their patient and participants' scanning experiences.